2004
DOI: 10.1677/joe.1.05683
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of somatotropic function in prion disease in sheep

Abstract: This study aimed at investigating the possible linkage between natural scrapie and alterations of the somatotropic axis. Scrapie-affected ewes exhibited 2-fold higher mean GH concentrations during both autumn and spring. GH pulse frequencies were higher in scrapie-affected ewes than in control animals (mean S.E.M. number of pulses/ 24 h: 10·4 0·9 and 7·6 0·9 for scrapie-affected and control ewes respectively) suggesting the involvement of central mechanisms. GH secretion induced by administration of an 2 -adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Specifically, in the 139H scrapie model, a severe preclinical anabolic syndrome was evident and was more pronounced when hamsters were non-fasted, whereas in the HY TME model a severe catabolic syndrome developed by clinical disease and was more pronounced when hamsters were fasted. Although endocrine data associated with glucostasis are scarce from other prion disease models, sheep with clinical scrapie disease appear to also have increased concentrations of insulin and are also hyperglycemic (Viguie et al 2004) although scrapie-infected sheep actually lose weight near clinical disease onset (Capucchio et al 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, in the 139H scrapie model, a severe preclinical anabolic syndrome was evident and was more pronounced when hamsters were non-fasted, whereas in the HY TME model a severe catabolic syndrome developed by clinical disease and was more pronounced when hamsters were fasted. Although endocrine data associated with glucostasis are scarce from other prion disease models, sheep with clinical scrapie disease appear to also have increased concentrations of insulin and are also hyperglycemic (Viguie et al 2004) although scrapie-infected sheep actually lose weight near clinical disease onset (Capucchio et al 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Although progressive neurological symptoms are typical of the prion diseases, disruption of endocrine homeostasis has been observed in many instances, including those that have either an acquired, spontaneous, or familial etiology. For example, in scrapie, a prion disease of sheep and goats, hypersecretion of cortisol (Schelcher et al 1999, Gayrard et al 2000, growth hormone (Viguie et al 2004), and insulin-like growth factors (Busiguina et al 2000) have been observed, as well as altered binding capacity of cortisol-binding globulin (Gayrard et al 2000). Endocrine alterations in hamsters infected with the 139H strain of the scrapie agent (hereafter, 139H scrapie) have also been reported (Carp et al 1989, Ye et al 1994a,b, 1997, Ye & Carp 1995; for reviews, see Carp et al 1990Carp et al , 1994 including obesity, pronounced hyperinsulinemia, altered glucose tolerance and/or insulin resistance (Carp et al 1989, Srinivasappa et al 1989.…”
Section: Introductionmentioning
confidence: 99%
“…This neuropathology in the pituitary gland is associated with hyperplasia and hypertrophy of islets of Langerhan cells, thyroid glands, adrenal glands, liver, and kidneys (Ye and Carp 1996). In addition, increased plasma levels of Gh, ACTH, and cortisol are evident during natural sheep scrapie (Gayrard et al 2000;Viguie et al 2004). Taken together, these studies indicate that alterations in the expression of pituitary hormones may be responsible for some of the clinical symptoms observed during scrapie infection in mice, hamsters, and sheep.…”
Section: Discussionmentioning
confidence: 92%
“…Multiple endocrine alterations have been reported to be common amongst prion and other neurodegenerative diseases [19,33,82,118,128]. A recent study by Viguié et al [118] investigated links between scrapie infection and alterations in somatotrophic function; it was reported that infected animals exhibited double the mean growth hormone (GH) concentration during anoestrous and breeding seasons.…”
Section: Blood Metabolitesmentioning
confidence: 99%
“…A recent study by Viguié et al [118] investigated links between scrapie infection and alterations in somatotrophic function; it was reported that infected animals exhibited double the mean growth hormone (GH) concentration during anoestrous and breeding seasons. Furthermore, plasma glucose, insulin and urea concentrations were reported to be higher in scrapie-affected ewes in comparison to controls [118]. This study demonstrates an association between endocrine and metabolic alterations and scrapie disease.…”
Section: Blood Metabolitesmentioning
confidence: 99%